NGO Politics in Sri Lanka Local Government and Development - Akurugoda, Indi Ruwangi (Springer International Publishing, 2018)
This book examines how and why local communities have been neglected in development initiatives in South Asia, focusing on Sri Lanka, and assesses the significant support from NGOs in increasing the capacity of local government and in promoting local development. Based on research in the southern and eastern provinces of Sri Lanka, this project analyses the views of national, provincial and local level political representatives, administrative officials, and NGO officials.